2018
DOI: 10.1186/s12864-018-5172-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of peripheral olfactory impairment in the domestic silkworms: insight from the comparative transcriptome and population genetics

Abstract: BackgroundThe insect olfactory system is a highly specific and sensitive chemical detector, which plays important roles in feeding, mating and finding an appropriate oviposition site. The ecological niche of Bombyx mori has changed greatly since domestication from B. mandarina, and its olfactory response to environmental odorants clearly decreased. However, the mechanisms that result in the olfactory impairment are largely unknown.ResultsThe antennal transcriptomes were compared between the domestic and wild s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…In insects, the characterization of metabolizing enzymes received an increasing interest with regard to their role in insecticide resistance, adaptation to host plant volatile and their function; as ODEs, in the termination of the olfactory signal to maintain a relatively high olfactory sensitivity toward new stimuli. In particular, recent studies investigating the antennal transcriptome in different species identified varied ODEs including CYP, CES, GST and UGT [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These reports have completed and confirmed the case-by-case identification of previously characterized ODEs [25][26][27][28][29][30][31].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In insects, the characterization of metabolizing enzymes received an increasing interest with regard to their role in insecticide resistance, adaptation to host plant volatile and their function; as ODEs, in the termination of the olfactory signal to maintain a relatively high olfactory sensitivity toward new stimuli. In particular, recent studies investigating the antennal transcriptome in different species identified varied ODEs including CYP, CES, GST and UGT [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These reports have completed and confirmed the case-by-case identification of previously characterized ODEs [25][26][27][28][29][30][31].…”
Section: Introductionsupporting
confidence: 59%
“…In any case, our data reveal that this mechanism likely depends on the level of the UGT gene product: males combining both the mutation and the RNAi targeted in neural tissues showed a wild-type-like behavioral discrimination. This is reminiscent of a recent transcriptomic study performed in the Bombyx mori silkworm antenna which revealed that the olfactory impairment observed in the domestic strain is correlated with a decreased expression of ODEs (including some UGTs) as compared to the wild B. mori strain [15].…”
Section: Involvement Of Odes In Pheromonal Signal Modulation Was Prevmentioning
confidence: 63%
“…At the same time, the olfactory response of S. bifasciatus populations from different places to the same attractant are varied (unpublished data). The genetic basis related to physiological differences of insects may be gene expression level differences or sequences variation [48][49][50]. We found that in males of S. bifasciatus, the expression levels of OBPs, ORs, and SNMPs of the Beijing population were obviously lower than those of the Shandong population, and most conserved SNPs of OBPs and ORs from the two populations were the ones that showed more diversity in the Beijing population.…”
Section: Discussionmentioning
confidence: 82%
“…Previous trapping variation in S. bifasciatus from two different sites indicated that the olfactory systems of these two populations were different (unpublished data). The reasons could be quantitative or qualitative diversities of their chemosensory genes [48][49][50]. Thus, to explore the quantitative differences in the olfactory systems of these two S. bifasciatus populations, we analyzed the expression levels of S. bifasciatus from the two sites.…”
Section: Discussionmentioning
confidence: 99%
“…In the silkworm, cocoon yield traits are also under control of domestication. Whole-genome resequencing of eight silkworm strains and seven wild silkworms from ecologically different regions has been conducted in our laboratory 36 . The selective sweep regions were identified in the whole genome, which showed extremely low heterozygosity and high F ST values relative to wild populations ( Fig.…”
Section: Resultsmentioning
confidence: 99%